A hybrid concentrated solar thermal collector/thermo-electric generation system. (1st September 2017) - Al-Nimr, Moh'd A.; Tashtoush, Bourhan M.; Khasawneh, Mohammad A.; Al-Keyyam, Ibrahim
Abstract: A bi-generation system combining direct absorption flat plate solar collector for medium temperatures air-heating applications integrated with a thermoelectric generator was modeled under optically concentrated solar radiation conditions. In order to improve the performance of the bi-generation system, the proposed system was simulated under the effect of evaporative cooling at the cold side of the thermoelectric modules in order to create a cooling effect that decreases the temperature of the cold junction, thus enhancing the electrical conversion efficiency of the thermoelectric modules. Rung-Kutta 4th order method is used to solve the ordinary differential, equation, while Newton-Raphson iterative technique is used to solve the nonlinear algebraic system of the model governing equations. The results have reflected a significant effect for the evaporative cooling on the system performance particularly at high values of optical concentration ratio. Furthermore, an augmentation of 19.13% in the total electrical power output was predicted at a concentration ratio of 20 suns. Simulation results had also shown that more stable electrical performance of the system when adopting evaporative cooling method compared to forced convection. It was found that there was an optimum value of water mass flow rate, at which the maximum power output was generated. Finally, relative humidity was shown to have a less significant impact on the performance at high temperature operation, since the effect of high water vapor partial pressure at the heat sink (cold junction), when the system is operating at elevated temperature, dominated over the effect of ambient relative humidity according to the evaporation rate governing model. Highlights: A 1-D mathematical model was developed to evaluate the system performance. The evaporative cooling has significant effect on the system performance. Wind speed plays a major role in the case of pure forced convection. Stable electrical performance for the system while adopting evaporative cooling. An optimal value of mass flow rate is found for maximum power output.